1991
DOI: 10.2307/5419
|View full text |Cite
|
Sign up to set email alerts
|

Foraging and Oviposition Decisions in the Parasitoid Aphytis lingnanensis: Distinguishing the Influences of Egg Load and Experience

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. SUMMARY(1) We used an experimental protocol that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
145
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(156 citation statements)
references
References 58 publications
8
145
3
Order By: Relevance
“…These inferences are in agreement with the study of ROSENHEIM & ROSEN (1991), who observed that the load of eggs influenced the intensity of the search behavior in the A. lingnanensis parasitoids, since the females with smaller load of eggs needed more time inside a foraging area to discover the host.…”
Section: Behaviorsupporting
confidence: 82%
See 4 more Smart Citations
“…These inferences are in agreement with the study of ROSENHEIM & ROSEN (1991), who observed that the load of eggs influenced the intensity of the search behavior in the A. lingnanensis parasitoids, since the females with smaller load of eggs needed more time inside a foraging area to discover the host.…”
Section: Behaviorsupporting
confidence: 82%
“…Notwithstanding, ROSENHEIM & ROSEN (1991) shows that the manipulation period with the host was inversely related to the load of eggs in the parasitoid A. lingnanensis, as well as of each component of the activities that comprise host manipulation, including preparation for oviposition, post-oviposition period, grooming and rest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations